Cosmotheology And Ecology: Exploring The Intersection Of Faith And Environment In The Barong Wae Culture Of East Manggarai Slope Community - Suratama, Eurico Suicang (Jurnal Indonesia Sosial Sains, 2025)
This paper aims to find out about the culture of barong wae in the theory of cosmotheology and ecology. The method used in this writing is literature study, the author collects literature related to the discussion that the author does. The results and discussion in this paper are, barong wae culture as an initial rite for major events such as the penti event which is a ceremony (thanksgiving for the harvest and celebration of the new year), and congko lokap which is a celebration (construction of a new traditional house called mbaru gendang). Theories on cosmotheology, ecology and barong wae culture are discussed in this paper. The study of the relationship between the universe and God is called cosmotheology, while ecology is the study of the relationship between organisms and their environment. This research discusses the barong wae rite, which is performed by the Manggarai people.